Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Kemampuan Siswa dalam Mengulas Karya Fiksi di Kelas VIII UPTD SMP Negeri 1 Gunungsitoli - Sesiwarniwati Gulo; Yanida Bu’ulolo; Noveri Amal Jaya Harefa; Mastawati Ndruru (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model on students' ability to review fictional works in class VIII of SMP Negeri 1 Gunungsitoli. This study uses a quantitative approach with a quasi-experimental method, with a non-equivalent control group design. The population in this study were all students of class VIII of SMP Negeri 1 Gunungsitoli, while the research sample consisted of two classes, namely class VIII-C as the experimental class and class VIII-F as the control class, each totaling 31 students. The research instrument used was a pretest and post-test in the form of essays. The results of the validity test showed that all test items were valid with a calculated r value > r table (example: question number 3 r count = 0.905 > r table = 0.367). The reliability test showed a value of α = 0.78 which means the instrument is reliable. The difficulty level ranged from 69.60% to 77.33% (moderate to easy category), and the discriminating power ranged from 0.20–0.32 (sufficient to moderate category). The average pretest score for the experimental class was 63.58, and the posttest score increased to 80.61. Meanwhile, in the control class, the average pretest score was 62.38, and the posttest score increased to 71.35. Based on the results of the independent t-test, t = 3.82 and t = 2.00 were obtained at a significance level of 5%.